Invisible Search and Online Search Engines: The Ubiquity of Search in Everyday Life, 1st edition - Haider, Jutta (Routledge, 2020)
Invisible Search and Online Search Engines considers the use of search engines in contemporary everyday life and the challenges this poses for media and information literacy. Looking for mediated information is mostly done online and arbitrated by the various tools and devices that people carry with them on a daily basis. Because of this, search engines have a significant impact on the structure of our lives, and personal and public memories. Haider and Sundin consider what this means for society, whilst also uniting research on information retrieval with research on how people actually look for and encounter information.